Information system supporting research on rubber in Thailand - Siriwan Kajornkasirat; Jirapond Muangprathub; Nathaphon Boonnam; Teerawad Sriklin (Institute of Advanced Engineering and Science, 2021)
his research aimed to develop an information system supporting research on rubber (ISSR) in Thailand. This system was designed as a web application with responsive web design. The rubber database was developed with MySQL, used Apache Server as a Web Server and programed with PHP-script. High Chart, Google Chart API and Java Technology were used to represent an online information with graphical format. The system was tested with the actual data on rubber research in Southern Thailand. The system has been available online at URL http://www.s-cm.site/issr. There are three type of users: administrator, researcher (member) and generic user. The researcher performed data entry about research with log-in to the system using username and password provided by the automatic system via online registration form. The administrator can manage the research information. The researchers can manage their research information, use searching tool and leave comments on other member’s research. The generic users can access the system without username and password to view the research and general information on rubber. Moreover, the system generates a report on rubber research with online graphical format. In conclusion, this information system enhances investigation on rubber research in Thailand and its strategy planning for rubber plantation in the future.